2002
DOI: 10.1002/jgt.10062
|View full text |Cite
|
Sign up to set email alerts
|

Circular chromatic number of distance graphs with distance sets of cardinality 3

Abstract: Suppose D is a subset of R þ . The distance graph G(R, D) is the graph with vertex set R in which two vertices x,y are adjacent if jx À y j 2 D. This study investigates the circular chromatic number and the fractional chromatic number of distance graphs G(R, D) with jDj ¼ 3. As a consequence, we determine the chromatic numbers of all such distance graphs. This settles a conjecture proposed independently by Chen et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
(33 reference statements)
1
19
0
1
Order By: Relevance
“…However, we do not know whether there is any other set M attaining this bound. It seems natural to conjecture the following: We note here that for m 3, both Conjectures 5.2 and 5.3 are true [5,7,28].…”
Section: Consequences and Related Problemsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, we do not know whether there is any other set M attaining this bound. It seems natural to conjecture the following: We note here that for m 3, both Conjectures 5.2 and 5.3 are true [5,7,28].…”
Section: Consequences and Related Problemsmentioning
confidence: 95%
“…Partial results on the circular chromatic number and the fractional chromatic number were obtained by Zhu [28].…”
Section: Consequences and Related Problemsmentioning
confidence: 98%
“…However, there is a very simple general coloring method that works for many distance graphs: the regular coloring method. This method was used to determine not only the chromatic number but also the circular chromatic number of many distance graphs [2,3,6,14,20,35]. The essence of the regular coloring method is revealed in the proof of Theorem 9 below, which was proved in [31].…”
Section: Proof It Was Proved Inmentioning
confidence: 99%
“…Their motivation was to study the one-dimensional analogue of the well-known plane coloring problem (i.e., finding the minimum number of colors needed to color the plane so that no two points of unit distance are colored the same color). Later on, it was found that the chromatic number and fractional chromatic number of distance graphs are related to many other problems, such as T -colorings [3,24], diophantine approximations [35], density of D-sets [15] and circulant graphs [20], etc.…”
Section: G(z D) For N ≥ 1 We Denote By G(n D) the Subgraph Of G(mentioning
confidence: 99%
“…[4] for recent results and many related references. Notably, the chromatic number of G(D) is now determined in [5] for all three-element distance sets D.…”
Section: E={(i J) | I < J J − I ¥ D}mentioning
confidence: 99%